Loss of B-cell Receptor Expression Defines a Subset of Diffuse Large B-cell Lymphoma Characterized by Silent BCR/PI3K/AKT Signaling and a Germinal Center Phenotype Displaying Low-risk Clinicopathologic Features. (July 2015) - Wang, Wei-Ge; Cui, Wen-Li; Wang, Lei; Zhu, Fen; Wan, Xiao-Chun; Ping, Bo; Zhou, Xiao-Yan; Li, Xiao-Qiu
Abstract : B-cell receptor (BCR) signaling is crucial for the survival of normal and neoplastic B cells, and inhibitors targeting BCR signaling pathways have shown promising therapeutic outcomes for patients with B-cell lymphomas. In the current study, we analyzed de novo diffuse large B-cell lymphoma without BCR expression (DLBCL, BCR − ) in 25 cases to determine the BCR/phosphatidylinositol-3-kinase/AKT (BCR/PI3K/AKT) signaling status, clinicopathologic features, and underlying causes leading to the loss of BCR. On the basis of clinical features, 15 (60%) DLBCL, BCR − patients were classified into the low-risk group, and 18 (86%) experienced complete remission. Morphologically and immunophenotypically, DLBCL, BCR − demonstrated centroblastic cytology (21/25, 84%) and germinal center B-cell-like cell origin (18/25, 72%). Other components in BCR complexity remained intact, on the basis of immunohistochemical findings. Epstein-Barr virus infection, deficiency in B-lineage transcription factors (PAX5, Oct-2, and Bob.1), and oncogene rearrangement did not seem to be associated with BCR loss. The activated form of signaling proteins (pSYK and pAKT) involved in the BCR/PI3K/AKT pathway were expressed at low levels in DLBCL, BCR − tissue. In vitro validation revealed that in DLBCL, BCR − cell lines, the BCR/PI3K/AKT pathway did not respond to BCR stimulation or inhibition. Our findings suggest that DLBCL, BCR − was characterized by a silent BCR/PI3K/AKT pathway, germinal center phenotype, and low risk and may not be a candidate for BCR-targeted therapies. Abstract : Supplemental Digital Content is available in the text.